A “Gastric” Novel. Phenomenology of Hunger and Disgust since Knut Hamsun’s (Itinera, 2017)
The novel Hunger by Knut Hamsun, published in 1890, marks a crucial phenomenon for the literature of the 20th Century. The essay aims at showing the central role of the hunger in the novelâs conception and writing. The phenomenology of hunger and disgust displayed by the Norwegian writer plays several symbolic functions: it appears as a physical sensation, a process of the life of the mind, a symbol of artistic creation and an ethical choice in front of the modern social disorder.Â